Patriarcavirus, feminist dystopias and COVID-19: Reflections on the phenomenon of gender pandemics - Machado-Jiménez, Almudena (Feminismo/s, 2021)
This essay examines contemporary feminist dystopias to study the phenomenon of gender pandemics. Gender pandemic narrative allegorises possible aftermaths of patriarcavirus, unleashing many natural disasters that force global biopolitics to hinder gender equality. The main objective of this essay is to explain how gender pandemics are appropriated in patriarchal utopian discourses as a pretext to control female empowerment, diagnosing women as diseased organisms that risk the state’s well-being. Moreover, the novels explore the interdependence between biology and sociality, portraying the acute vulnerability of female bodies during and after the pandemic conflicts, inasmuch as patriarchal power arranges a hierarchical value system of living that reinforces gender discrimination. Particularly, the COVID-19 emergency is analysed as a gender pandemic: the exacerbated machismo and the growing distress in the female population prove that women are afflicted with a suffocating patriarcavirus, which has critically gagged them in the first year of the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; arts; corps; covid-19; discipline; droits des femmes*; genre; patriarcat; précarité; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques; violences; études littéraires

Kuei, je te salue: conversation sur le racisme - Béchard, Deni Ellis; Kanapé Fontaine, Natasha (Collection Parcours (Éditions Écosociété), 2020)
« En 2016, la poète lnnu Natasha Kanapé Fontaine et le romancier québéco-américain Deni Ellis Béchard entamaient une conversation sans tabou sur le racisme entre Autochtones et Allochtones. Comment cohabiter si notre histoire commune est empreinte de honte, de blessures et de colère? Comment faire réaliser aux Blancs le privilège invisible de la domination historique? Comment guérir les Autochtones des stigmates du génocide culturel? Ces questions traversent leurs échanges: Natasha raconte sa découverte des pensionnats autochtones, son obsession pour la crise d'Oka, la vie dans la communauté de Pessamit ; Deni parle du racisme ordinaire de son père, de la ségrégation envers les Afro-Américains, de son identité de Québécois aux États-Unis. Cinq ans plus tard, Deni et Natasha reprennent la plume pour poursuivre ce "rendez-vous de la parole qui s'ouvre". Renouant avec le ton intimiste et le foisonnement intellectuel de leur premier échange, ils abordent des sujets d'une brûlante actualité: mobilisation de Black Lives Matter après la mort de George Floyd, feux de forêt en Californie, campagne présidentielle sur fond de montée de l'intolérance; soulèvement des Wet'suwet'en et blocus ferroviaires, dénonciation de la politique de la reconnaissance du gouvernement Trudeau. Puis survient l'impensable: Joyce Echaquan, une Atikamekw de 37 ans, meurt sous les injures racistes de deux infirmières de l'hôpital de Joliette. Une vague d'indignation monte ...»--Quatrième de couverture.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

Robert McRuer on Crip Theory - CP-assistenten (2016)
Interview of Robert McRuer on crip theory.
Keywords: EDI; approches et analyses; arts; capacitisme; cours; discipline; histoire et politique; premier cycle; ressource en ligne; santé; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires